Biennial reports of the Chief of Staff of the United States Army to the Secretary of War : 1 July 1939-30 June 1945 - Marshall, George C. 1880-1959 (CMH Pub, 1996)
July 1, 1939 to June 30, 1941 -- The First phase -- State of the armed forces, July 1, 1939 -- The President's emergency proclamation September 8, 1939 -- The Second phase -- The President's messages of May 16, and May 31, 1940 -- Progress during the winter of 1940-41 -- Special problems incident to the expansion -- Reorganization of command and staff -- State of the armed forces July 1, 1941 -- Recommendations for the elimination of certain legal limitations and restrictions -- Appendix -- July 1, 1941 to June 30, 1943 -- The Third phase -- Extension of service -- Development of the army -- Reinforcements for overseas garrisons -- Time factor -- Changing situation -- The Fourth phase -- War is declared -- Strategy and control -- Global war -- Struggle for the Philippines -- Coral Sea -- high tide of aggression -- The Fifth phase -- The Solomons -- Papua -- European theater -- North African theater -- Middle East -- Asiatic theater -- Operations in Alaska -- Conclusion -- organization -- Logistics -- Training -- Air forces -- Planning -- July 1, 1943, to June 30, 1945 -- Victory in Europe -- Strategic concept -- Fall of Italy -- Operation OVERLORD -- Victory over Japan -- The Road to China -- Unremitting pressure -- Occupation -- Our weapons -- The Troops -- For the common defense -- Charts -- Maps